1983
DOI: 10.1093/jac/12.suppl_a.269
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of ceftazidime into human tissue in patients undergoing cardiac surgery

Abstract: The penetration of ceftazidime into human heart muscle, skeletal muscle, skin, fat and bone was measured in 39 patients undergoing cardiac surgery. Mean serum levels of 70 mg/l were measured 1.5 h after dosing with mean levels of 27 mg/l after 4 h and 5.5 mg/l after 12 h. Tissue levels of ceftazidime were measured up to 280 min after dosing. These levels were high with mean corrected levels after 120 min of 20.0 mg/l in bone, 7.1 mg/l in skin (after 100 min), 9.2 mg/l in fat, 12.7 mg/l in heart muscle and 9.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…After a single intravenous dose of 2 g of ceftazidime it was found that in the myometrium, endometrium and salpinges, the tissue penetration is similar (0.34±0.43 quotient tissue/serum) to that we found in lung [6]. The concentration in cardiac muscle is 33% of that in serum and that in bone 60% [1]. In the mouse, the per centage penetration of ceftazidime from serum into the lung tissue is 17% and for the rabbit it is 11.3 % [9,10].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…After a single intravenous dose of 2 g of ceftazidime it was found that in the myometrium, endometrium and salpinges, the tissue penetration is similar (0.34±0.43 quotient tissue/serum) to that we found in lung [6]. The concentration in cardiac muscle is 33% of that in serum and that in bone 60% [1]. In the mouse, the per centage penetration of ceftazidime from serum into the lung tissue is 17% and for the rabbit it is 11.3 % [9,10].…”
Section: Discussionsupporting
confidence: 69%
“…Many ways have been described for trying to eliminate it from the samples of lung tissue, such as drying them with a gauze, washing them repeat edly, expressing them, etc. [1,6], We washed and dried the samples but even so the homogenate showed a high content of hemoglobin (from 6.5 to 66.6% compared to that of blood), which has posed a statis tically significant correction factor in all the samples and in some cases also in the mean values. On the contrary other au thors hold that the blood content of the samples of tissue is of less importance [1].…”
Section: Discussionmentioning
confidence: 99%
“…Aztreonam concentrations in cancellous bone (mean, 20% of that in concomitant serum) are similar to those of moxalactam (18%) (21), cefazolin (18%) (21), cefadroxil (23%) (23), cephalothin (5 to 33%) (7,9,26), cefamandole (5 to 20%) (18,24,26), cefuroxime (10 to 70%) (7), clindamycin (10 to 50%) (1,28), ceftazidime (54%) (1), and amoxicillin (16.4%) (2). However, the ranges for all these antibiotics were very wide (25,28), with some specimens showing no detectable concentrations.…”
mentioning
confidence: 69%
“…In general, single-dose (versus multiple-dose) studies (8,21) and studies that corrected for blood contamination (1,21,24) detected lower penetration values. In dogs, cefazolin, penicillin, and cefamandole in serum rapidly equilibrate with the interstitial fluid of bone (5,11,16).…”
mentioning
confidence: 97%
“…This factor could therefore account for a more rapid trans port and distribution of antibiotic into heart muscle and heart muscle fluid. In this regard, a recent clinical study in pa tients undergoing cardiac surgery [1] sug gested that ceftazidime concentrations in cardiac muscle were slightly but not sig nificantly higher than in skeletal muscle.…”
Section: Discussionmentioning
confidence: 95%